Results of computer simulation for test signal models of passive interferences within analog-to-digital conversion - Барышев, И.В.; Щербина, К.А.; Мсаллам, Е.П.; Нежальская, К.Н.; Вонсович, М.А.; Инкарбаева, О.С. (Radiotekhnika, 2019)
This work includes analysis of the possibility for practical implementation of a simplified test model for the sea surface remote sensing by a real coastal radar; digital models of the test signal have been developed taking into account the features of the analog-to-digital video signal conversion; simplified digital test models of radar reflections from the sea surface are proposed. The results of the research will be further used for solving the problem of determining the coordinates of the extended marine objects location, as well as in solving similar problems of digital radar technology design.